Recovery of insoluble-bound phenolics and bioactive volatile compounds from MD2 pineapple peel by enzyme-assisted extraction and kinetic model - Nordin, Nur Liyana; Sulaiman, Rabiha; Noranizan, Mohd Adzahan; Bakar, Jamilah (Springer, 2023)
Pineapple peel is a natural source of bioactive compounds. This study aimed to evaluate the effect of cellulase and pectinase in the extraction of phenolics and volatile compounds from pineapple peel. The parameters employed were enzyme concentrations, solid to solvent ratios (SSR), extraction temperatures and time. Cellulase improved the extraction process at a treatment of 1.5% (v/v) enzyme concentration, a 1:4 g/mL of SSR, an extraction temperature and a time of 50 °C and 120 min, respectively. Through second-order kinetic modelling (r2 = 0.9189), the maximised yield of phenolics was 8.72 mg GAE/g per dry weight basis (DW) as extracted by cellulase. Insoluble-bound phenolics (IBP) extraction after the cellulase treatment increased significantly (p < 0.05) by 99.79% as compared to non-enzyme treatment. GC-MS analysis revealed 22 bioactive volatile compounds. The compounds identified were acetic acid, followed by sterols (stigmasterol, β-sitosterol and γ-sitosterol) and esters (benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, methyl ester and 1,2-benzenedicarboxylic acid). Therefore, the results of cellulase extraction of bioactive volatile compounds from pineapple peel waste have the potential as an added value ingredient in food, cosmetics and pharmaceutical applications.